The dynamics of velocity development in elite women sprinters - Stoyanov, H. (New Studies in Athletics, 2015)
This study builds on previous work conducted on male sprinters, which revealed differences in each phase of the 100m between the champions at major international events and those who medalled. Data on a total of 31 performances by several generations of top women sprinters at the IAAF World Championships in Athletics and Olympic Games were analysed. The objectives were to study the velocity dynamics and identify the factors that distinguish the very top women sprinters and thus the priorities for the planning of training programmes. According to the results, the start and the subsequent acceleration were important for the final result, since within the first 10m of the distance the athletes attained a high percentage (47.36%) of their maximum velocity. Also important is the ability to maintain the level of velocity attained for as much of the distance as possible. The author concludes with the hope that the analysis will help coaches develop methods to best prepare sprinters to match the requirements of each phase of the ideal competition model he provides.